2011
DOI: 10.1097/cmr.0b013e328347ee53
|View full text |Cite
|
Sign up to set email alerts
|

Role of H4 receptor in histamine-mediated responses in human melanoma

Abstract: We have previously reported that histamine at micromolar concentrations reduces the proliferation of melanoma cell lines. It is also known that melanoma cells express histamine H 1 , H 2 , and H 3 receptors. The aim of this study was to investigate the presence of histamine H 4 receptor (H 4 R) in human melanoma cells and its associated biological processes. To better understand the importance of histamine in tumor development, we explored the expression of H 4 R in human melanoma tissue biopsies. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…The H 4 receptor has been shown to mediate cell cycle arrest in hematopoietic progenitor cells induced by growth factors (Petit-Bertron et al, 2009). In addition, activation of the receptor appears to inhibit proliferation of several human cancer cell lines (Massari et al, 2011(Massari et al, , 2013. The release of adrenocorticotropic hormone from a mouse pituitary tumor cell line via H 4 receptor activation has also been reported (Meng et al, 2008).…”
Section: Functionmentioning
confidence: 99%
“…The H 4 receptor has been shown to mediate cell cycle arrest in hematopoietic progenitor cells induced by growth factors (Petit-Bertron et al, 2009). In addition, activation of the receptor appears to inhibit proliferation of several human cancer cell lines (Massari et al, 2011(Massari et al, , 2013. The release of adrenocorticotropic hormone from a mouse pituitary tumor cell line via H 4 receptor activation has also been reported (Meng et al, 2008).…”
Section: Functionmentioning
confidence: 99%
“…Although there are several studies describing the action of histamine as a modulator of proliferation of certain tumors, its role in malignant melanoma is still inconclusive [5, 8, 9, 10]. It seems that histamine effect on tumor proliferation depends on the cell type, the balance between different receptor subtypes expressed, the concentration of histamine reached in the tumoral environment and the effectors activated, among others.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, it was demonstrated by using histamine agonists, antagonists and genetic tools, that histamine treatment produced an inhibitory effect on proliferation mediated in part through the stimulation of the H 4 R in WM35 and M1/15 human melanoma cells. In vivo experiments on M1/15 human primary melanoma experimental model demonstrated that mice receiving histamine or clozapine (H 4 R agonist) showed an increased median survival associated to a decrease in tumor growth and intratumoral neovascularization [8, 9]. In line with these results, numerous phase II and III clinical trials in metastatic melanoma demonstrated clinical benefits of histamine (Ceplene, a synthetic derivative of histamine) as an adjuvant to immunotherapy with IL-2, especially in melanoma patients with liver metastases [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 Also, the influence of H4 receptor-mediated inhibition of proliferation has been demonstrated in melanoma and breast cancer cells. 70 …”
Section: Histamine In Neoplasiamentioning
confidence: 99%